Virtual Simulation in Undergraduate Medical Education: A Scoping Review of Recent Practice - Wu, Qingming; Wang, Yubin; Lu, Lili; Chen, Yong; Long, Hui; Wang, Jun (Frontiers in Medicine, 2022)
Virtual simulation (VS) as an emerging interactive pedagogical strategy has been paid more and more attentions in the undergraduate medical education. Based on the fast development of modern computer simulation technologies, VS-based instructional practices in diverse forms are continuously adopted to promote the training of future medical professionals. In order to describe an overview of the current trends in VS-based medical education, this scoping review presented a worldwide analysis of 92 recently published articles of VS in the undergraduate medical teaching and learning. The results indicated that 98% of included articles were from Europe, North America and Asia, suggesting a possible inequity in VS-based medical education. Half (52%) studies reported the immersive virtual reality application. Evidence for educational effectiveness of VS in medical students’ knowledge or skills was sufficient as per Kirkpatrick’s model of outcome evaluation. Recently, VS has been widely integrated in surgical procedural training, emergency and pediatric emergency medicine training, teaching of basic medical sciences, medical radiation and imaging, puncture or catheterization training, interprofessional medical education, and other case-based learning experiences. Some challenges, such as accessibility of VS instructional resources, lack of infrastructure, “decoupling” users from reality, as well as how to increase students’ motivation and engagement, should be addressed.